Understanding visitors’ motivations of sharing experiences related to Hungarian tourism events and festivals - Iványi, Tamás; Bíró-Szigeti, Szilvia (Publishing House of Wroclaw University of Economics and Business, 2021)
For Generation Z (born after 1995) tourism during the summer usually means visiting festivals (especially music festivals) seeking extraordinary experiences. For them the classic tourist attractions are not satisfying and interesting anymore. The aim of the paper was to examine the measurement methods for sharing experiences related to these festivals and tourist programmes, and understand how other tourists use these shared experiences during the information gathering phase. The methodology is based on literature review and quantitative primary research. A structured questionnaire was used for the quantitative research focusing on the motivations of sharing travel experience and sources of information gathering. The data were collected by means of an on line survey via LimeSurvey, and descriptive statistics was used to interpret the acquired data. As a result of the quantitative research, three different groups of Hungarian youngsters visiting local music festivals were formed. For them, sharing that experience means different things: some only create memories for themselves, some try to create valuable content that may help others, and some want to become a social media celebrity. They use social media and they also gather information in a different way. Knowing how these groups use social media to share experiences and to get information are key factors for marketing managers in order to use an efficient communication method with each group. It is also an important factor to understand the differences in people’s motivations with the aim to create a well-planned marketing campaign.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 81-106
Keywords: customer motivations; festival tourism; generation Z; social media; tourism experience